An in vitro DNA sensor-based assay to measure receptor-specific adhesion forces of eukaryotic cells and pathogens - Wack, Maurizio; Wiegand, Tina; Frischknecht, Friedrich; Cavalcanti-Adam, Elisabetta A. (Bio-protocol, 2020)
Motility of eukaryotic cells or pathogens within tissues is mediated by the turnover of specific interactions with other cells or with the extracellular matrix. Biophysical characterization of these ligand-receptor adhesions helps to unravel the molecular mechanisms driving migration. Traction force microscopy or optical tweezers are typically used to measure the cellular forces exerted by cells on a substrate. However, the spatial resolution of traction force microscopy is limited to ~2 µm and performing experiments with optical traps is very time-consuming. Here we present the production of biomimetic surfaces that enable specific cell adhesion via synthetic ligands and at the same time monitor the transmitted forces by using molecular tension sensors. The ligands were coupled to double-stranded DNA probes with defined force thresholds for DNA unzipping. Receptor-mediated forces in the pN range are thereby semi-quantitatively converted into fluorescence signals, which can be detected by standard fluorescence microscopy at the resolution limit (~0.2 µm). The modular design of the assay allows to vary the presented ligands and the mechanical strength of the DNA probes, which provides a number of possibilities to probe the adhesion of different eukaryotic cell types and pathogens and is exemplified here with osteosarcoma cells and Plasmodium berghei Sporozoites.
Gesehen am 28.10.2025